The TNF-α antagonist etanercept decreases blood pressure and protects the kidney in a mouse model of systemic lupus erythematosus - Venegas-Pont, Marcia (2010)
Chronic inflammation has been implicated in the pathology of hypertension; however, the role for specific cytokines remains unclear. We tested whether TNF-α blockade with etanercept (Etan) reduces mean arterial pressure (MAP) in a female mouse model of systemic lupus erythematosus (SLE). SLE is a chronic inflammatory disorder with prevalent hypertension. Thirty week old SLE (NZBWF1) and control mice (NZW/LacJ) received Etan (0.8mg/kg SC weekly) for 4 weeks or vehicle. MAP (mmHg) was increased in SLE mice (150±5 vs. 113±5 in controls, p<0.05) and was lower in Etan treated SLE mice (132±3) but not controls (117±5). Albuminuria (µg/mg creatinine) was elevated in SLE mice (28742±9032 vs. 1075±883 p<0.05) and was lower in Etan treated SLE mice (8154±3899) but not control animals (783±226). Glomerulosclerosis (% of glomeruli) was evident in SLE mice (2.5±1.6 vs. 0.0±0.0 in controls, p<0.05) and was ameliorated in Etan treated SLE mice (0.1±0.1). Renal cortex CD68+ cell staining (% area) was elevated in SLE mice (4.75±0.80 vs. 0.79±0.12 in controls, p<0.05) and was lower in Etan treated SLE mice (2.28±0.32) but not controls (1.43±0.25). Renal cortex NADPH oxidase activity (RLU/mg of protein) was higher in SLE mice compared to controls (10718±1276 vs. 7584±229, p<0.05) and lowered in Etan treated SLE mice (6645±490). Renal cortex NFκB (phosphorylated and non-phosphorylated) was increased in SLE mice compared to controls and lower in Etan treated SLE mice. These data suggest that TNF-α mechanistically contributes to the development of hypertension in a chronic inflammatory disease through increased renal NFκB, oxidative stress and inflammation.